Legal Dimensions of CSR: Impacts on Corporate Performance and Stakeholder Trust - Lestari, Putri Ayu (Sinergi International Journal of Law, 2024)
Corporate Social Responsibility (CSR) has evolved from a voluntary philanthropic endeavor to a strategic component deeply embedded in legal and regulatory frameworks. This study aims to explore the role of the legal dimension in CSR implementation and its influence on organizational performance and stakeholder perceptions. Employing a narrative review methodology, the research systematically analyzed peer-reviewed literature from major academic databases including Scopus, Web of Science, and Google Scholar. Through Boolean logic and thematic filtering, the study identified trends and patterns related to legal compliance, organizational commitment, and public trust. The results reveal that legal CSR contributes significantly to internal operational efficiency, enhances employee commitment, and elevates public acceptance. Legal compliance also serves as a strategic tool in reputation management and stakeholder engagement. However, systemic barriers such as inconsistent regulations, lack of institutional coordination, and limited legal expertise hinder optimal implementation. Policy instruments including mandatory reporting, fiscal incentives, and international standard adoption (e.g., GRI) have proven effective in enhancing compliance. Furthermore, public trust and legal knowledge act as key mediators, bridging the gap between policy and perception. This review underscores the necessity of a holistic policy approach and calls for reform in regulatory frameworks and organizational capacity building. The findings provide valuable insights for policymakers, corporate leaders, and scholars seeking to align legal frameworks with sustainable CSR practices.